DRUGS LAW AND LEGAL PRACTICE IN SOUTHEAST ASIA: INDONESIA, SINGAPORE, AND VIETNAM - Maskun, Maskun (Indonesia Law Review, 2017)
Drugs Law and Legal Practice in Southeast Asia investigates criminal law and practice relevant to drugs regulation in three Southeast Asian jurisdictions: Indonesia, Singapore and Vietnam. These jurisdictions represent the spectrum of approaches to drugs regulation in Southeast Asia, highlighting differences in practice between civil and common law countries, and between liberal and authoritarian states.